Potential effects on groundwater quality associated with infiltrating stormwater through dry wells for aquifer recharge - Edwards, Emily C.; Nelson, Connie; Harter, Thomas; Bowles, Chris; Li, Xue; Lock, Bennett; Fogg, Graham E.; Washburn, Barbara S. (Journal of contaminant hydrology, 2022)
Dry wells (gravity-fed infiltration wells) have frequently been used to recharge aquifers with stormwater, especially in urban areas, as well as manage flood risk and reduce surface water body contamination from stormwater pollutants. However, only limited assessment of their potential adverse impacts on groundwater quality exists. Dry well recharge can bypass significant portions of the filtering-capacity of the vadose zone. Stormwater and groundwater monitoring data and analysis of transport of a wide range of historic and current-use stormwater chemicals of concern is lacking. To address these gaps, two dry wells were constructed with vegetated and structural pretreatment features to assess the likelihood of stormwater contaminants reaching the aquifer. We monitored, assessed, and compared the presence of contaminants in stormwater to water quality in the vadose zone and shallow groundwater after it passed through the dry well. The dry wells were installed at a suburban residential and at a suburban commercial site. The selected sites were overlying a regional, unconsolidated, and highly heterogeneous alluvial aquifer system. Stormwater, vadose zone, and groundwater samples were collected during five storms and analyzed for over 200 contaminants of concern. Relatively few contaminants were detected in stormwater, generally at low concentrations. Prior to stormwater entering the dry well, 50–65% of contaminants were removed by vegetated pretreatment. In groundwater, metals such as aluminum and iron were detected at similar concentrations in both upgradient and downgradient wells, suggesting the source of these metals was not dry well effluent. Naturally occurring metals such as chromium and arsenic were not detected in stormwater but were found at elevated concentrations in groundwater. A modeling assessment suggests that the travel time of metals and hydrophobic organic contaminants to the water table at these sites ranges from years to centuries, whereas water soluble pesticides would likely reach the water table within days to months. The modeling assessment also showed that more vulnerable sites with higher fraction of alluvial sands would have much shorter contaminant travel times. However, none of the contaminants assessed reached concentrations that pose a risk to human health across the scenarios considered. No evidence was found, either through direct measurements or vadose zone modeling, that contaminants present in suburban stormwater degraded or would degrade groundwater quality at the studied sites and site conditions. Future work is needed to address emerging contaminants of concern. •Infiltration of stormwater runoff through dry wells with pretreatment may pose little risk to groundwater quality.•Pretreatment and subsurface clay sequester particles and reduce the concentration of pollutants reaching the aquifer.•Modeling suggests most contaminants take decades to centuries to reach the water table, given sufficient subsurface clay.